ANALISIS PENYELIDIKAN KARAKTERISTIK TANAH KOTA DENPASAR MENGGUNAKAN METODE BOR TANGAN, DAN UJI LABORATORIUM - UMPUR, LEONARDA SAPUTRI; KURNIARI, KRISNA; DIPUTERA, I GEDE ANGGA; LESTARI, I GUSTI AGUNG ISTRI; WARID, MOH; NADA, I MADE (GANEC SWARA, 2024)
Soil investigations in the form of hand boring, SPT tests, and laboratories were carried out on Jalan Pura Demak Denpasar City. The purpose of this study is to determine the characteristics of the soil in the area. Handboring results showed 0 to 2.5 m of clay soil, depth of 2.5 to 3.5 m of sandy silt rock tuff, depth of 3.5 to 4 m sandy clay, depth of 4 to 10 m sandy rock. SPT test results obtained values of 12 at depths of 0 to 2.5 m, at depths of 2.5 to 3.4 m are 40 and at depths of 4 to 10 m are 43-50. Based on laboratory tests, the following soil characteristics were obtained: the moisture content at a depth of 1 m is 39.65% and at a depth of 5 m is 15.39%. Specific gravity at a depth of 1 m = 2.778, at a depth of 5 m = 2.543. Compressive strength 0.310 kg/cm2 and cohesion 0.155 kg/cm2 at a depth of 1 m. Direct shear strength at a depth of 5 m, cohesion of 0.00 kg/cm2 and shear angle of 35.30°. The results of the filter analysis for sample tests at a depth of 1 m were 80.69% clay, 13.96% silt, 5.05% fine sand, and 0.40% medium sand. At a depth of 5 m is loam + silt 29.80%, fine sand 22.47%, medium sand 25.25%, coarse sand 8.08%, and small gravel 14.39%.